Korelasi antara kadar plasma NT-proBNP dengan Kecepatan Doppler Jaringan di anulus katup mitral pada penderita Gagal Jantung - Raja Adil C Siregar; Harmani Kalim; Bambang Budi Siswanto; Amiliana M Soesanto (Jurnal Kardiologi Indonesia, 2010)
Background.N-terminal pro brain natriuretic peptide (NT-proBNP) will release from myocite granules in a condition of increased cardiac wall-stress in heart failure (HF) patients, and its plasma level elevation had been widely used as a parameter of diagnosis, functional class, treatment monitoring and prognostication. Pulsed-wave tissue Doppler velocities of mitral annulus (Tissue Doppler Imaging/TDI) currently known had an ability to detect move-ment changes of cardiac wall in HF patients. But only few research to see the correlation between them, with various selection of patients and results.Aim. To determine whether plasma NT-proBNP levels correlate with mitral annulus velocities measured by TDI and to search which component had the strongest correlation.Methods.One hundred consecutive patients with HF who came for echocardiography examination in The National Cardiac Center Harapan Kita Jakarta underwent an additional TDI procedure (Sm, Emand E/Em component). Before or after echocardiography, venous blood sample was collected for plasma NT-proBNP examination. We determined the cor-relation between plasma NT-proBNP level and TDI results, and assessed which component had the strongest correlation.Results.There were 74 men and 26 women of HF patients with mean of age 54 y.o. Functional NYHA Class II were 28 patients, NYHA Class III 42 patients and NYHA Class IV 30 patients. The causes of HF were CAD 49 patients, HHD 19 patients, Valve Disease 23 patients, DCM 8 patients and other 1 patient. There were 64 patients with sinus rhythm and 36 patients with atrial fibrillation. There were 17 diastolic HF patients and 83 systolic HF patients. Fifty patients with significant MR and 50 patients without significant MR. We found the strongest significant negative correlation (r= -0,713, p0,000) between plasma NT-proBNP level and Emcomponent. Smalso had a significant negative correlation, but Emhad a stronger correlation than Sm. E/Emcomponent had a weak significant positive correlation.Conclusion.Elevated plasma NT-proBNP levels correlates strongly with declining velocities of TDI early diastolic Emcomponent in HF patients.